Recycling resources: silica of diatom frustules as a source for spicule building in Antarctic siliceous demosponges. Issue 2 (20th October 2020) - Riesgo, Ana; Taboada, Sergi; Kenny, Nathan J; Santodomingo, Nadia; Moles, Juan; Leiva, Carlos; Cox, Eileen; Avila, Conxita; Cardona, Luis; Maldonado, Manuel
Abstract: Dissolved silicon (DSi) is biologically processed to produce siliceous skeletons by a variety of organisms including radiolarians, silicoflagellates, choanoflagellates, plants, diatoms and some animals. In the photic ocean, diatoms are dominant consumers over competing other silicifiers. In Antarctica, where DSi is not particularly limiting, diatoms and sponges coexist in high abundances. Interestingly, diatom ingestion by sponges is a regular feeding strategy there. Although it was known that the diatom organic nutrients are readily metabolized by the sponges, what happened to the inorganic diatom silica skeleton remained unexplored. Here, we have conducted a multi-analytical approach to investigate the processing of diatom silica and whether it is reconverted into sponge silica. We have documented widespread diatom consumption by several demosponges, identifying storage vesicles for the diatom-derived silica by electron microscopy and microanalysis. Diatom-consuming sponges showed upregulation of silicatein and silicase genes, which in addition to the δ 30 Si values of their silica, supports that the sponges are converting the ingested diatom silica into sponge silica without much further Si fractionation. Our multidisciplinary approach suggests that the reutilization of diatom silica by sponges is a common feature among Antarctic sponges, which should be further investigated in other latitudes and in other silicifiers.